The influence of shifting Pacific identities in learning : the experience of parents raising children of mixed Pacific ethnicities : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Education at Massey University, Palmerston North, New Zealand - Leafe, Rachael Violeti (Massey University, 2017)
Identity construction for the Pacific population in Aotearoa/New Zealand remains a politically and contextually contested arena that shifts according to the socio-cultural interactions within the immediate and external environment of an individual. This study views parents as agents of change and explores ethnic transmission and cultural identity development through the eyes of parents raising children of mixed Pacific ethnicities. This qualitative study employed both Western and Pacific methodologies to collect and analyse data and used the talanoa method to engage the insights and experiences of five couples. Social constructionism and Bronfenbrenner’s (2005) ecological systems theory provided a framework to explain the dynamics of social interactions and external conditions that influence the constructs of peoples’ lived realities. This study found that families, peers, and schools influence interactions that shift and impact the cultural identity development and resiliency of children with mixed Pacific ethnicities. In addition to this, societal perceptions, racism, and stereotypes are external environmental conditions that further impact cultural identity development and resiliency. The metaphor of a balancing act illustrates the challenges and strategies parents use to manage family and cultural expectations as well as the efforts required to maintain access and opportunities to cultural knowledge, values and practices. The findings suggest that a culturally responsive education can work to minimise intolerance, exclusion, and racism experienced by an individual. Key recommendations include the promotion of identity development education that serves to empower individuals and parents to nurture positive identities and resilience in the mixed Pacific generation.
Keywords: Pacific Islanders; Racially mixed children; Ethnic identity; Education; Parents; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education